Broadband PLC Network Cross-Layer Simulation in Accordance with the IEEE P1901 Standard - Gogić, A.; Mujčić, A.; Zajc, M.; Suljanović, N. (Elektronika ir Elektrotechnika, 2013)
This paper presents the discrete-event simulator of the low-voltage broadband power line communication (BPLC) access network in accordance with the IEEE P1901 standard. The proposed simulator enables the cross-layer simulation of the physical (PHY) and medium access control (MAC) layer. The performance of the digital communication techniques at the physical layer and the characteristics of the shared medium are integrated at the MAC layer through the probability of the bit error. The proposed simulator was applied in order to estimate the throughput in the simple BPLC network. For the selected set of parameters at the MAC and PHY layer in the test network, the simulator recorded average download throughput of 900kbps, registration time of 36ms and packet delivery ratio of for 0.98 between each station and the HE. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1440